1839. Expanding Antimicrobial Stewardship into the Community: Development of Patient and Provider Education Resources to Improve Antibiotic Awareness. (26th November 2018) - Gentry, Erin; Sweeney, Chloe; Pion, Sonya; Spencer, Melanie; Handy, Elizabeth; Davis, Marion; Yates, Traci; Davidson, Lisa
Abstract: Background: Antibiotic stewardship programs are vital in the ambulatory setting to address the public health threat of antibiotic resistance. In 2016, the Centers for Disease Control and Prevention (CDC) released Core Elements of Outpatient Antibiotic Stewardship. These core elements were the basis for the development of the Carolinas HealthCare Outpatient Antimicrobial Stewardship Empowerment Network (CHOSEN), which collaborates with more than 150 Atrium Health ambulatory practices to improve antibiotic awareness across metropolitan, suburban and rural communities, touching approximately 1, 060, 000 patients. Methods: Initial baseline research involved surveys with 190 patients and key informant interviews with four patients and 17 providers. A resource working group was formed during a follow-up strategic planning session involving more than 40 multidisciplinary stakeholders. Key concepts identified through patient and provider engagement were the focus for the development of stewardship education and resources with involvement from physicians, nurses and pharmacists, as well as representation from quality, marketing and patient experience. Results: Identified opportunities were addressed with the design of a "Bacteria and Viruses" patient handout and symptoms checklists for over-the-counter recommendations for adults, teens and children—all with translation into an additional 11 languages; a commitment flyer for patient examination rooms; pediatric dosing guides for acetaminophen and ibuprofen; provider scripting; and two educational videos. Resources were introduced via a consumer webpage, a provider intranet site update, and media pitching featuring key providers in the community to coincide with the CDC's National Antibiotic Awareness Week in November 2017. Additional focused provider and practice-site education sessions were held for ambulatory practice specialties of urgent care, family medicine, internal medicine and pediatrics. Conclusion: Through multidisciplinary collaboration, CHOSEN developed a better understanding of patient and provider attitudes and experiences that led to the development of specific tools and a campaign to meet the identified needs for antibiotic awareness in the community. Disclosures: E. Gentry, Duke Endowment: Grant Investigator, Grant recipient. C. Sweeney, Duke Endowment: Grant Investigator, Grant recipient. M. Spencer, Duke Endowment: Grant Investigator, Grant recipient. Eli Lilly and Company: Grant Investigator, Grant recipient. E. Handy, Duke Endowment: Grant Investigator, Grant recipient. L. Davidson, Duke Endowment: Grant Investigator, Grant recipient.